Silica fume and waste glass in cement concrete production: A review - Mehta, Ankur; Ashish, Deepankar Kumar (Journal of Building Engineering, 2020)
The vast emission of greenhouse gases from industrial wastes is a global problem. The non-biodegradable nature of industrial wastes like silica fume, glass, bottom ash, and rubber tyres increases the severity of the problem. Past studies suggest that the use of waste materials in the cement and construction industry could be a viable solution to prevent natural resources from extinction. The chemical composition of silica fume and waste glass are attracting cement and concrete industries as a sustainable solution. In recent years, green concrete is very popular among researchers and academicians, but green concrete is still at an early stage. This paper studies the influence of silica fume and waste glass on the workability, strength, and durability properties of concrete. Moreover, the microstructural analysis was also studied. •The influence of silica fume and waste glass on the fresh and hardened properties of concrete were studied.•The strength properties of concrete improved with the inclusion of silica fume and waste glass up to a certain content.•Workability of concrete decreases with the addition of silica fume whereas it increases with the inclusion of waste glass.